2014
DOI: 10.1038/eye.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

In vitro optical performance of a new aberration-free intraocular lens

Abstract: Purpose To assess the optical performance of the new EnVista intraocular lens (IOL). Materials and methods Four aspheric IOLs were evaluated; the new EnVista is one amoung them. This IOL, similarly to the Z-Flex HB and the Bi-Flex 1.8 667AB ones, has a neutral aspheric design, whereas the fourth IOL under test (AcrySof IQ IOL SN60WF) presents a negative spherical aberration (SA). The IOL's aberration patterns were measured in vitro, by setting them up on an optical bench. From these aberration-pattern data, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…An in vitro study showed the superiority of the Acrysof spherical aberration-correcting IOL over the Envista IOL, when the average spherical aberration of the cornea was added to an eye model. 25 The results of tilt in our study are in accordance with an earlier study investigating the crystalline lens and IOL tilt measured by anterior segment optical coherence tomography. Both crystalline lens and IOL showed a tendency to tilt toward the inferotemporal direction.…”
Section: Resultssupporting
confidence: 92%
“…An in vitro study showed the superiority of the Acrysof spherical aberration-correcting IOL over the Envista IOL, when the average spherical aberration of the cornea was added to an eye model. 25 The results of tilt in our study are in accordance with an earlier study investigating the crystalline lens and IOL tilt measured by anterior segment optical coherence tomography. Both crystalline lens and IOL showed a tendency to tilt toward the inferotemporal direction.…”
Section: Resultssupporting
confidence: 92%
“…The measurement of the MTF at a particular spatial frequency as a function of defocus is known as the through-focus MTF. 8 Several studies [9][10][11][12][13][14][15][16][17][18] have evaluated the throughfocus MTF to determine the optical quality of IOLs.…”
mentioning
confidence: 99%
“…12 On the other hand, EnVista is an aberration-free aspherical IOL to retain minor positive SA for the eyes to maximize the depth of focus. 15 A unique feature of EnVista, stated by its manufacturer, is called glistening-free property. [13][14][15]31 Glistenings are micro-vacuoles that appear within an IOL material, and are commonly seen in hydrophobic acrylic IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…15 A unique feature of EnVista, stated by its manufacturer, is called glistening-free property. [13][14][15]31 Glistenings are micro-vacuoles that appear within an IOL material, and are commonly seen in hydrophobic acrylic IOLs. They may cause forward-scattering of the light going to the eye, and accordingly degrade visual function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation